STUDI KELAYAKAN PENGEMBANGAN WISATA ALAM DI TAMAN NASIONAL BOGANI NANI WARTABONE (Lokasi : Camping Ground Bolonsio) - Kusmayanti ., Kusmayanti; Paulus Adrian Pangemanan; Wenny ., Tilaar (AGRI-SOSIOEKONOMI, 2021)
This study aims to analyze the feasibility of developing natural tourism in the Bogani Nani Wartabone National Park at the Bolonsio Camping Ground location. This research was conducted from February to March 2021. The research method used is the data collected consisting of Primary Data and Secondary Data, which were obtained by several methods, namely field observation methods, interview methods and literature studies. The results of the assessment show that the study location is feasible to be developed even though there are still quite a lot of things concerning the implementation or practice of ecotourism, which are classified as not being optimally carried out in natural tourism objects that are being studied and require improvement and improvement of various factors included in the aspect of accessibility. This is of course a separate homework for managers of tourism objects, in order to make efforts to develop natural tourism that pays attention to aspects of tourism management that actually carry out the principles of ecotourism.